VALUATION OF THE YOUTH’S SELF-IDENTITY VIA PRINCIPAL COMPONENT ANALYSIS - Ahmad Zaharuddin Sani Ahmad Sabri; Shamshuritawati Sharif; Roziya Abu; Rozira Abu (Proceeding International Conference on Information Technology and Business, 2020)
Self-identity is believed to be an important determinant of psychological well-being that is mostly challenging during young life stage. Youth with high self-identity able to develop positive attitude such as self-confidence, more optimist, and accept disagreement. Therefore, in this study, Northern Region of Peninsular Malaysia was investigated to identify the most influential factors that contributing to the youth’s self-identity. The data first investigate by using descriptive statistics followed by a multivariate statistical analysis. Principal component analysis (PCA) was utilized to simplify the complex relationship among 35 self-identity parameters. Based on 63.85 total variation in the data, the results show that youth’s self-identity are influent by four main factors which are religion, patriotism, economy and government aids. This study presents the usefulness of PCA in evaluating the factors of self-identity. It is valuable for educators to conceive optimum action plans for controlling low self-identity in future generation. Finding of this study on the self-identity of young generation in the state of Kedah are discussed. Taking into consideration are the complexity of Malaysian society, one that consists of differences in ethnicity, class, education, religion, language and geographical location, which in itself produces young Malaysians of various identities.Keywords: Youth, Self-identity, multivariate statistics, principal component analysis